Single dose oral etoricoxib for acute postoperative pain in adults. - Clarke, R; Derry, S; Moore, R; McQuay, H (2009)
BACKGROUND: Etoricoxib is a selective cyclo-oxygenase-2 (COX-2) inhibitor prescribed for the relief of chronic pain in osteoarthritis and rheumatoid arthritis, and acute pain. The drug is believed to be associated with fewer upper gastrointestinal adverse effects than conventional non-steroidal anti-inflammatory drugs (NSAIDs). A number of studies in acute postoperative pain have now been published. OBJECTIVES: To assess the analgesic efficacy and adverse effects of a single oral dose of etoricoxib for moderate to severe postoperative pain. SEARCH STRATEGY: We searched Cochrane CENTRAL, MEDLINE, EMBASE, and the Oxford Pain Database, and reference lists of articles. Date of the most recent search: December 2008. SELECTION CRITERIA: Randomised, double-blind, placebo-controlled clinical trials of single dose, oral etoricoxib for acute postoperative pain in adults. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trials for inclusion in the review and quality, and extracted data. The area under the pain relief versus time curve was used to derive the proportion of participants prescribed etoricoxib or placebo with at least 50% pain relief over six hours, using validated equations. Relative risk (RR) and number needed to treat to benefit (NNT) were calculated. Information on use of rescue medication was used to calculate the proportion of participants requiring rescue medication and the weighted mean of the median time to use. Information on adverse effects was also collected. MAIN RESULTS: Five studies (880 participants) were included in the review. All five studies reported on 120 mg, with 655 participants in a comparison with placebo. At least 50% pain relief was reported by 64% with etoricoxib 120 mg and 10% with placebo (NNT 1.9 (1.7 to 2.1)). For dental studies only the NNT was 1.6 (1.5 to 1.8). Two studies also reported on higher doses of 180 and 240 mg, with 249 participants. At least 50% pain relief was reported by 79% with etoricoxib 120 mg and 12% with placebo (NNT 1.5 (1.3 to 1.7)).Significantly fewer participants used rescue medication when taking etoricoxib 120 mg than those taking placebo (NNT to prevent remedication 2.4 (2.1 to 2.9)), and the median time to use of rescue medication was 20 hours. Adverse events were reported at a similar rate to placebo, with no serious events. AUTHORS' CONCLUSIONS: Single dose oral etoricoxib produces high levels of good quality pain relief after surgery. The 120 mg dose is as effective as, or better than, other commonly used analgesics.